Metal Oxide Thin Films: Synthesis, Characterization and Applications - Rauwel, habil. Erwan; Rauwel, Protima (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
This Special Issue will compile recent developments in the field of metal oxide thin film deposition. The articles presented in this Special Issue will cover various topics, ranging from, but not limited to, the optimization of deposition methods, thin film preparations, the functionalization of surfaces with targeted applications, nanosensors, catalysis, electronic devices, biocidal coating, and the synthesis of nanostructures via the accurate control of thin film deposition methods, among others. Topics are open to metal oxide thin film deposition and characterization for the development of applications.